Theological Reflection A Franciscan Perspective - Park, Sophia S.; Mayer, Suzanne (2018)
In life, where disappointments, unexpected challenges, and even tragedies abound, how do we, as pastoral counsellors/theological educators, teach our students to care for themselves and their clients when reality upends their lives? The Franciscan tradition has stood for almost 800 years, beginning with the Poor Man of Assisi's response to a direct call from God in the midst of his own and the world's tragedies. So, too, with life: the truth revealed on the underside can open a capacity for meaning, one embracing healing, resilience, and growth. The theological reflection process fosters such outcomes, awakening new understandings about the circumstances in which persons live and suggesting new ways of responding. From this emerges the underside of grace, meaning made not in spite of pain, but through it. The vision held within a process of theological reflection allows the person faced with the underside of life to see patterns of truth and grace.
Keywords: Franciscan; Grace; image-making; Praxis; Resilience; Suffering; Theological Reflection